2019
DOI: 10.1155/2019/9549315
|View full text |Cite
|
Sign up to set email alerts
|

Screening Five Qi-Tonifying Herbs on M2 Phenotype Macrophages

Abstract: Tumor-associated macrophages (TAMs) with M2 phenotype play an essential role in tumor microenvironment (TME) during the progression and development of numerous cancers and associated with poor prognosis. Thus, regulation of TAMs polarization emerged as a new strategy for tumor immune therapy. According to Traditional Chinese Medicine (TCM) theory, herbs with Qi-tonifying character are involved in improving the defense capacity of immune system. In this study, we screened extracts and ingredients from five Qi-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…The transcription and production of TGF-β and IL-10, two well-known immunosuppressive cytokines secreted by TAMs, were reduced in response to Panax polysaccharides and also the number of infiltrated CD168+ M2 TAMs was substantially declined although the number of CD68+ total macrophages in transplanted tumor tissues remained almost unchanged [81]. A significant inhibition of Arg-1 expression (above 90% at 100 μg/mL), one of the phenotype markers of M2 macrophages, was also observed for the ethanol extract of Ginseng Radix et Rhizoma [62]. Recently, Chen et al [82], showed that water extract of Ginseng and Astragalus could be a novel option for integrative cancer therapies due mainly to their ability to regulate macrophage polarization.…”
Section: Polysaccharidesmentioning
confidence: 69%
See 1 more Smart Citation
“…The transcription and production of TGF-β and IL-10, two well-known immunosuppressive cytokines secreted by TAMs, were reduced in response to Panax polysaccharides and also the number of infiltrated CD168+ M2 TAMs was substantially declined although the number of CD68+ total macrophages in transplanted tumor tissues remained almost unchanged [81]. A significant inhibition of Arg-1 expression (above 90% at 100 μg/mL), one of the phenotype markers of M2 macrophages, was also observed for the ethanol extract of Ginseng Radix et Rhizoma [62]. Recently, Chen et al [82], showed that water extract of Ginseng and Astragalus could be a novel option for integrative cancer therapies due mainly to their ability to regulate macrophage polarization.…”
Section: Polysaccharidesmentioning
confidence: 69%
“…Total flavonoids from Glycyrrhizae Radix et Rhizoma significantly inhibited the expression of Arg-1 (above 90% at 100 μg/mL), one of the phenotype markers of M2 macrophages, and suppressed M2 polarization of macrophages partly by inactivating STAT6 pathway. The regulation of M1 and M2 markers' expressions was partly due to the enhancement of miR-155 levels [62].…”
Section: Flavonoidsmentioning
confidence: 98%
“…Curcumin, DHA, EGCG, resveratrol, and silibinin have been shown to modulate more than two components of the TME. As a single herb, Glycyrrhiza Radix et Rhizoma exhibited the most potent effect in the normalization of TAMs (Jiang et al, 2019). Hochu-ekki-to (Bojungikki-tang) and Keishi-bukuryo-gan (Gyejibokryeong-hwan) can reverse the immunosuppressive function of MDSCs (Koga et al, 2017), while HangAmDan-B can promote M1 polarization (Park et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, epoxydocosapentaenoic acid treatment interfered with the interaction between VEGF and VEGF receptor 2, resulting in impaired tumor angiogenesis (Zhang et al, 2013a). macrophage-induced 4T1 breast cancer cell migration (Jiang et al, 2019).…”
Section: Epoxydocosapentaenoic Acidsmentioning
confidence: 99%
“…In addition, accumulating evidence has suggested that the polarized-M2 phenotype could increase the proliferation, migration and invasion abilities of cancer cells. 18,23,46 Zhao et al [47][48][49] found that M2-TAMs enhanced metastasis by improving the migration capacity of breast cancer 4T1 cells. In addition, Pang et al 46 found that culturing NSCLC cells with M2-polarized TAMconditioned medium (TAM-CM) ultimately led to stronger proliferation, migration, and invasion than culturing these cells in routine medium (Figure 2).…”
Section: Direct Effects Of M1-tams and M2-tams On Cancer Cellsmentioning
confidence: 99%